TWITTER INFORMATION SYSTEM ANALYSIS OF STUDENTS IN BUSINESS - Nurhasanah, Adinda Mutiara; Rizki, Denu Nur; Andriani, Dina (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This study aims to determine the impact of the Twitter information system on business students. A qualitative descriptive method is employed to characterize this occurrence using a survey in the form of a Google form-distributed questionnaire. A simple random sample of 30 questionnaires was delivered to 30 respondents as part of the sampling process. Perceptions of benefits and perceptions of convenience are used to identify application users and Twitter social media users among students. The current data is then evaluated more thoroughly in order to draw conclusions. The results indicate that the perception of benefits indicates that 90.7% of students agree that the Twitter information system helps to attract business, while the perception of convenience indicates that 85% of students find it easier to locate information that is being discussed, particularly business-related information. Students conducting business in the city of Tasikmalaya are impacted in their use of the Twitter information system by two perceptions: advantages and convenience.